MINERAL TRANSFORMATIONS ASSOCIATED WITH THE MICROBIAL REDUCTION OF MAGNETITE - Dong H.; Fredrickson J.K.; Kennedy D.W.; Zachara J.M.; Kukkadapu R.K.; Onstott T.C. (My University, 2000)
Although dissimilatory iron reducing bacteria (DIRB) are capable of reducing a number of metals in oxides and soluble forms, the factors controlling the rate/extent of magnetite reduction and the nature of the mineral products resulting from magnetite reduction are not well understood. This study was carried out to investigate mechanisms and biogeochemical processes occurring during magnetite reduction by the DIRB, Shewanella putrefaciens strains CN32 and MR-1. Reduction experiments were performed with biogenic and synthetic magnetite in well-defined solutions. Biogenic magnetite was generated via microbial reduction of hydrous ferric oxide (HFO). Biogenic magnetite in solutions buffered with either bicarbonate (HCO3-) or 1,4-piperazinediethanesulfonic (PIPES), with or without P, was inoculated with strain CN32 and provided with lactate as the electron donor. Synthetic magnetite in a bacteriological growth medium (M1) was inoculated with either aerobically or anaerobically grown cells of strain (CN32 or MR-1). Fe(II) production was determined by HCl extraction of bioreduced samples in comparison to uninoculated controls, and the resulting solids were characterized by X-ray diffraction (XRD), Mossbauer spectroscopy, scanning and transmission electron microscopy (SEM and TEM). The extent and rate of biogenic magnetite reduction in the bicarbonate-buffered medium was higher than that in the PIPES-buffered medium, via complexation of bioproduced Fe(II) with HCO3- (or PO43-) and formation of siderite (vivianite). S. putrefaciens CN32 reduced more synthetic than biogenic magnetite with differences attributed mainly to medium composition. In the HCO3--buffered solutions, Fe(III) in the biogenic magnetite was reduced to Fe(II), and siderite precipitated. In the PIPES-buffered medium, Fe(III) in biogenic magnetite was also reduced to Fe(II), but no secondary mineral phases were observed. Vivianite formed in those solutions containing P and in all synthetic magnetite treatments where there was sufficient supply of P from the M1 medium. Electron microscopy and Mossbauer spectroscopy results suggest that the reduction process involves dissolution-precipitation mechanisms as opposed to solid state conversion of magnetite to vivianite or siderite. The aqueous medium, pH, strain type, and bacterial growth conditions all affected the extent of magnetite reduction. The ability of DIRB to utilize Fe(III) in crystalline magnetite as an electron acceptor could have significant implications for biogeochemical processes in sediments where Fe(III) in magnetite represents the largest pool of electron acceptor.
Keywords: SHEWANELLA PUTREFACIENS; REDUCTION; MAGNETITE; SIDERITE; VIVIANITE